#1**+1 **

The easiest way to do this is to square both sides but you have to check the answers that you get because some may be invalid.

Melody Dec 2, 2019

#2**0 **

Squaring both sides as melody said. we get:

(2x+1)^2=(2x+1)(2x+1)=4x^2+2x+2x+1=4x^2+4x+1

(4x+3)^2=(4x+3)(4x+3)=16x^2+12x+12x+9=16x^2+24x+9

So we have

\(4x^2+4x+1=16x^2+24x+9\)

Subtract 1

\(4x^2+4x=16x^2+24x+8\)

subtract 4x

\(4x^2=16x^2+20x+8\)

Rearrange

\(16x^2+20x+8=4x^2\)

Subtract 4x^2

\(12x^2+20x+8=0\)

Factor 4

\(4(3x^2+5x+2)\)=0

\(3x^2+5x+2=0\)

x=\(\frac{-2}{3}\) or -1

Subsituite back and check

2(-1)+1=4(-1)+3

-1 = -1 correct!

-1 is a solution

Subsituite -2/3 and check, Correct!

Guest Dec 2, 2019